FIXED POINT THEOREMS FOR GENERALIZED WEAKLY CONTRACTIVE CONDITION IN ORDERED PARTIAL METRIC SPACES - Aydi, H. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, we establish some fixed point theorems for generalized weakly contractive condition in ordered partial metric spaces. The results extend the main theorems of Nashine and Altun[17] on the class of ordered partial metric ones. Also, some applications are given to illustrate our results.